Determination of alpha hemoglobin stabilizing protein (AHSP) gene expression and oxidative stress parameters in HbE/beta-Thalassemia - Yaacob, Nur Suraya Che (2021)
Beta-Thalassaemia is the genetic disorders of haemoglobin synthesis characterized by reduced or absent β-globin chain synthesis thus lead to imbalance of tetramer. The Alpha Haemoglobin Stabilizing Protein (AHSP) acts as a molecular chaperone for α-globin by stabilizing free α-globin preventing it from precipitating and forming reactive oxygen species byproducts with subsequent oxidative damage and the formation of intracellular precipitates thus led to oxidative stress. Real time PCR and ELISA assay were used to determine the AHSP expression and oxidative stress parameters (SOD activity and MDA concentration) in blood sample respectively. Expression of AHSP significant in disease severity (p=0.001), transfusion dependency (p=0.033), molecular profile (p=0.035) and age (p=0.034), SOD activity significant in disease severity (p=0.005), transfusion dependency (p=0.001), serum ferritin level (p=0.005) and age (p=0.040), and MDA concentration significant in disease severity (p=0.003), transfusion dependency (p=0.001), splenectomy status (p=0.002), serum ferritin level (p=0.002) and age (p=0.015). We found that AHSP expression was significantly correlated to HbF (p=0.033) and frequency of blood transfusion per year (0.011) while SOD activity significantly correlated with age (p=0.033), HbF (p=0.009) and frequency of blood transfusion per year (p=0.004). On the other hand, MDA concentration was significantly correlated with age (p=0.008) and serum ferritin (p=0.022). In addition, correlation study was evaluated between AHSP expression with SOD activity and MDA concentration in which AHSP expression was significantly correlated with both parameters when p=0.002 and p=0.001 respectively. Thus, we concluded that AHSP could be a secondary compensatory mechanism in red blood cells to counterbalance the excess α-globin chains thus reduced the oxidative stress in HbE/Beta-Thalassaemia individuals. AHSP modifier and oxidative stress parameters give the future insight on its role in disease pathogenesis.